Gis-based model for optimal collection and transportation system for solid waste in allahabad city - Chaudhary S.; Nidhi C.; Rawal N.R. (My University, 2025)
Solid waste management (SWM) is one of the major problems faced by many countries in the world. The functional element of solid waste collection process includes not only the gathering of waste from the source, but also the transportation of these waste to common collection sites. It has been estimated that about 60–80% money spent for only the collection, and transportation of solid waste to the total amount is spent on the SWM system. An effective municipal solid waste management system is composed of optimized routes, systematic collection, transport, and transfer of wastes. The geographical information system (GIS) can be effectively applied for cost minimization and maximization of waste collection and transportation efficiencies in any area. The route optimization depends on many factors, including the location of waste bins, collection details, types of vehicle, travel impedances, and integrity of road network. In this study, to design better travel routes in city for enhance efficiency by GIS to develop model for collection and transportation of waste using Esri’s ArcGIS 3.2, Network Analyst software. The ArcGIS is used to determine optimal zones and optimal routes for each zone. In addition, a simple optimal routing model is proposed to achieve the minimum transportation cost, distance, time, and number of vehicles. The developed model may be utilized by MSW management agencies for optimized waste collection and transportation activities. © Springer Nature Singapore Pte Ltd. 2019.